Strength of Learning and Growth Metrics in Non-Financial Organizational Performance (PYC Nepal Journal of Management, 2022)
An organization can track its plan, communicate its progress and position, and record the actions and behaviors of its personnel by using performance measurement and management tools. The study's objective was to determine how an employee of a company learns and grows throughout his/her career to enhance the organization's overall performance. The quantitative research approach was followed, and data were collected by an organized questionnaire survey. Three hundred and three responses, utilizing the convenience sampling technique, were gathered from the working representatives of two large telecommunication service provider companies in Nepal. The study observed 17 learning and growth performance parameters to evaluate the non-financial organizational performance model. The model yielded statistically noteworthy ratios at p ≤ 0.05 for all measured parameters and supported hypothesized paths. The usage of non-financial performance metrics is growing, and it is not typical to use them as the primary metric for evaluating organizational performance. Hence, future researchers are advised to incorporate non-financial and financial metrics into organizational performance assessment and management systems.